LITERASI KIMIA MAHASISWA PGSD DAN GURU IPA SEKOLAH DASAR PADA TEMA UDARA - Sujana, Atep (Universitas Pendidikan Indonesia, 2014)
This study aims to determine the chemical literacy of primary school teachers and students on the theme PGSD air. The method used is descriptive method, the research subjects totaling 61 people, 41 people came from PGSD students and 20 people from elementary school teachers. The instrument used is a matter of chemistry literacy tests are 40 multiple -choice questions that include reason or other information to strengthen the answers given, questionnaires, and interviews. Data processing techniques performed included determination of the limits of chemical literacy achievement, scoring each question,changing the score values, grouping study subjects based on the values obtained, and the analysis and conclusions. From the research data showed that only 26 people (63.41 %) students who have achieved literacy PGSD chemistry, whereas only 10 elementary school teachers (50 %) who had reached chemical literacy. Literacy chemical that has not reached most of the research subject primarily determine the chemical formula of constituent gases of air and to write the equation.Keywords: PGSD students, elementary science teachers, science literacy, literacy chemistry, descriptive method.